2019
DOI: 10.1002/cncr.32675
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of barriers and facilitators to clinical trial enrollment among adolescents and young adults with cancer: Identifying opportunities for intervention

Abstract: Adolescents and young adults (AYAs) are underrepresented in cancer clinical trials (CCTs). Limited trial enrollment slows progress in improving survival rates and prevents the collection of valuable biospecimens. A systematic literature review was conducted to assess barriers and facilitators to AYA enrollment in CCTs and to identify opportunities to improve enrollment. The PubMed MEDLINE, Web of Science, Scopus, and PsycINFO databases were searched to identify studies relevant to AYA CCT enrollment. Eligibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 46 publications
(194 reference statements)
1
67
0
2
Order By: Relevance
“…However, previous research suggests that many AYA trials are available at the national level, but sites are not opening these trials locally and struggle to enroll eligible AYAs ( 23 , 27 ). A recently completed systematic review found this to be a consistently reported barrier across studies ( 13 ). Stakeholders also noted that only COG members could enroll on COG-led trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous research suggests that many AYA trials are available at the national level, but sites are not opening these trials locally and struggle to enroll eligible AYAs ( 23 , 27 ). A recently completed systematic review found this to be a consistently reported barrier across studies ( 13 ). Stakeholders also noted that only COG members could enroll on COG-led trials.…”
Section: Discussionmentioning
confidence: 99%
“…The interview guide for each stakeholder was informed by a systematic review ( 13 ), drafted by the study investigators (EJS, HLK, MR, ITM) and reviewed by the study team for relevance. The interview guides were slightly modified for each stakeholder group to ensure relevance to the stakeholder’s role in enrollment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst barriers to TYA's enrolment in cancer trials are relatively well-documented, a recent systematic review highlighted a paucity of studies attending to facilitators (Siembida et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst barriers to TYA’s enrolment in cancer trials are relatively well‐documented, a recent systematic review highlighted a paucity of studies attending to facilitators (Siembida et al, 2020). Though various commentators have hypothesised how access might be improved (Burke et al, 2007; Davis et al, 2017; Freyer & Seibel, 2015; Gupta & Indelicato, 2014), empirically informed recommendations remain limited.…”
Section: Introductionmentioning
confidence: 99%